Adoption and Utilization of an Emergency Department Naloxone Distribution and Peer Recovery Coach Consultation Program. (3rd October 2018) - Samuels, Elizabeth A.; Baird, Janette; Yang, Eunice S.; Mello, Michael J.
Abstract: Objective: Rising rates of opioid overdose deaths require innovative programs to prevent and reduce opioid‐related morbidity and mortality. This study evaluates adoption, utilization, and maintenance of an emergency department (ED) take‐home naloxone and peer recovery coach consultation program for ED patients at risk of opioid overdose. Methods: Using a Reach Effectiveness Adoption Implementation Maintenance (RE‐AIM) framework, we conducted a retrospective provider survey and electronic medical record (EMR) review to evaluate implementation of a naloxone distribution and peer recovery coach consultation program at two EDs. Provider adoption was measured by self‐report using a novel survey instrument. EMRs of discharged ED patients at risk for opioid overdose were reviewed in three time periods: preimplementation, postimplementation, and maintenance. Primary study outcomes were take‐home naloxone provision and recovery coach consultation. Secondary study outcome was referral to treatment. Chi‐square analysis was used for study period comparisons. Logistic regression was conducted to examine utilization moderators. Poisson regression modeled utilization changes over time. Results: Most providers reported utilization (72.8%, 83/114): 95.2% (79/83) provided take‐home naloxone and 85.5% (71/83) consulted a recovery coach. There were 555 unique patients treated and discharged during the study periods: 131 preimplementation, 376 postimplementation, and 48 maintenance. Postimplementation provision of take‐home naloxone increased from none to more than one‐third (35.4%, p < 0.001), one‐third received consultation with a recovery coach (33.1%, 45/136), and discharge with referral to treatment increased from 9.16% to 20.74% (p = 0.003). Take‐home naloxone provision and recovery coach consultation did not depreciate over time. Conclusions: ED naloxone distribution and consultation of a community‐based peer recovery coach are feasible and acceptable and can be maintained over time.